Mapping Muslim Perspectives on Gender Issues in Malang State Universities, Indonesia - Anggraeni, Luciana (UIN Sunan Gunung Dajti Bandung, 2025)
This study investigates the comprehension of gender-related matters among Muslim students in Malang State Universities, namely Brawijaya University, Malang State University, and the Islamic State University of UIN Maulana Malik Ibrahim. The study employs qualitative research methods, such as interviews and focus group discussions, to examine a range of viewpoints, beliefs, and attitudes regarding gender roles, equality, and related subjects. The findings demonstrate a range of understandings that are shaped by religious doctrines, cultural standards, and educational contexts. At Brawijaya University, students support progressive viewpoints that promote gender equality and question traditional male-dominated beliefs, resulting in their active participation in gender activism. Malang State University showcases a combination of conventional and innovative interpretations, with differing levels of endorsement for gender equality. Meanwhile, UIN Maulana Malik Ibrahim's Islamic State University adheres to conservative interpretations that prioritise traditional gender roles, leading to minimal involvement in gender activism. Religious and cultural factors overlap to shape attitudes regarding gender, as local norms and traditions have an impact on ideas of gender roles. Educational settings are of great importance, as Brawijaya University offers a favorable atmosphere for thoughtful examination of gender-related matters, whereas the Islamic State University places emphasis on Islamic morals and principles.